Introduction: Scholarly Communication and the STM Serials Pricing Crisis - Lorimer, Rowland (Canadian Journal of Communication, 1997)
This paper introduces the scientific, technical, and medical (STM) serials pricing crisis, distinguishing it from a temporary crisis in 1996 in humanities and social science publishing in Canada and from the general constraints operating on scholarly publishing. It then reviews the papers selected for inclusion in this volume.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjIyMzAvY2pjLjE5OTd2MjJuM2E5OTk